Antibodies to a human liver membrane lipoprotein (LSP) in primary biliary cirrhosis. Issue 7 (July 1980) - Tsantoulas, D; Perperas, A; Portmann, B; Eddleston, A L; Williams, R
Abstract : Antibodies reacting with a human liver-specific membrane lipoprotein (LSP) have been detected using a sensitive and specific radioimmunoassay in 19 (51%) of 37 patients with primary biliary cirrhosis. The anti-LSP antibodies were found only in the later stages of the disease as judged by histological criteria, being present in 73% of those in stage IV, 44% of those in stage III, and none of those in stage I or II. Although there was no relationship between percentage binding and standard liver function tests, there was a close correlation between percentage binding of 125I-LSP by serum and the extent of piecemeal necrosis of periportal hepatocytes on liver biopsy. The timing of the anti-LSP response makes it very unlikely that it is involved in the pathogenesis of the early bile duct damage but the results of this and other studies suggest that antibodies to this hepatocyte membrane lipoprotein may be an important cause of periportal liver cell necrosis in both primary biliary cirrhosis and chronic active hepatitis and could be one of the factors determining progression to cirrhosis in both these conditions.